A Statistical analysis on optical disc development corporation - Dy, Glady; Sim, Eleanor; Tan, Katheryn (Diliman, Quezon City College of Engineering, 2001)
Design of Experiment is concerned mainly on analyzing a process and determining how the inputs or factors affect the responses. Through the knowledge and proper application of this approach, the system of a company can be improved.The team studied on Optical Disc Development Corporation, a company that manufactures optical disc for a large number of recording companies in the country. Quality has been a major concern for the company, thus rejections cannot be avoided. Rejection causes loss to the company and should be given much attention. Using Problem analysis tools and techniques, the team was able to identify the main cause of rejection-electrical errors, and was further narrowed down to the specific parameters where most of the errors occur. The group focused on electrical errors since once it is detected, the whole batch of discs is rejected for that particular title. The only factor that affects electrical errors was found out to be the machines. This in turn will cause a big loss for the company. Limited data were provided by the company regarding the results of reading electrical signals. These were analyzed by determining the response variable, the level of significance as well as the power. The team had observed that only the machine can contribute to the electrical errors causing the rejection of CDs. Appropriate design was used which is the Fixed effects model of Single factor experiment. Further analysis was made using Analysis of Variance, regression methods and Duncan's Multiple range Test. The group was able to show through calculations that the all of the machine has the same effect on SLD, I11R and RN. However, in MID error, calculations show that machine 2 deviates the most from the specified mean. Using Operating Characteristics Curves, the group found out that 60 observations are needed to come up with a more accurate result of the tests conducted. Thus, the group recommends adding samples to have more reliable results for this study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics